PVDF-HFP-(at) PEG-based electrolyte, preparation method thereof and lithium battery

By adopting the 'slight crosslinking method' in the field of lithium metal battery electrolytes, NH2-PEG-NH2 and PVDF-HFP are specially bonded to form PVDF-HFP-@PEG-based mild crosslinking polymer electrolytes, solving the problems of high crystallinity, low electrolyte affinity, and poor interface stability with the electrodes, achieving multi-faceted performance improvement of electrolytes and the optimization performance of lithium metal batteries.

CN119833740AActive Publication Date: 2025-04-15FUZHOU UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510011391.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-15
Estimated Expiration
2045-01-03

AI Technical Summary

Technical Problem

The polymer electrolytes of existing polymer-based lithium metal batteries have disadvantages in terms of high crystallinity, low affinity of the electrolyte, and poor interface stability with the electrode, resulting in limited performance such as power density, cycle life and safety.

Method used

Using the ‘slight crosslinking method’ strategy, a PVDF-HFP-@PEG-NH2 is used to form a PVDF-HFP-@PEG-based mild crosslinking polymer electrolyte by special bonding between double-terminal amino polyethylene glycol (NH2-PEG-NH2) and polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP). This method successfully achieved multi-faceted performance improvement of the electrolyte without introducing a catalyst or crosslinking agent.

Benefits of technology

It significantly improves the mechanical properties, electrochemical properties, chemical/thermal stability of PVDF-HFP-@PEG-based electrolyte, optimizes the key electrochemical properties of lithium metal batteries, and improves the long-term stable cycle performance and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833740A_ABST
    Figure CN119833740A_ABST
Patent Text Reader

Abstract

The invention discloses a PVDF-HFP-coated PEG-based electrolyte, a preparation method thereof and a lithium battery, and belongs to the technical field of electrolyte preparation. The preparation method comprises the following steps: blending two polymer phases through a solvent to obtain a precursor solution, continuously and uniformly stirring at normal temperature, and pouring a film; then sequentially performing normal-temperature drying and high-temperature crosslinking under a vacuum condition to obtain a polymer base membrane; and soaking the obtained base membrane in an electrolyte for a period of time to obtain a target polymer electrolyte, and finally cutting the target polymer electrolyte into an electrolyte sheet with a certain size and further assembling the electrolyte sheet into the lithium metal battery. The invention provides a novel cross-linking strategy, namely a'slight cross-linking method ', amino-terminated polyethylene glycol and a PVDF-HFP matrix are combined to form a cross-linked polymer with a stable structure under the condition that a catalyst or a cross-linking agent is not introduced, and the ionic conductivity, the mechanical property and the chemical / thermal stability of the electrolyte can be remarkably improved. The method is expected to realize important breakthrough of the corresponding lithium metal battery in the aspects of fast charging performance, cycle life and safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium battery polymer electrolyte materials, and mainly relates to a preparation method of a corresponding cross-linked polymer electrolyte formed by special bonding between double-terminated amino polyethylene glycol (NH2-PEG-NH2) and polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), and its application in metal batteries. Background Art

[0002] The development of the next generation of electrochemical energy storage technology is of great strategic significance to the country's social and economic development. As an important development direction of electrochemical energy storage technology, the development and application of energy storage and power batteries have received widespread attention from the government, scientific research, and business fields. Among them, lithium-ion batteries have attracted widespread attention as a typical representative. However, at present, lithium-ion batteries are mainly liquid batteries based on volatile organic electrolytes, and the energy density that can be achieved is only 250Wh / kg. In addition, there are hidden dangers in safety, which can no longer fully meet people's urgent needs for high-performance energy storage devices. In recent years, polymer-based lithium metal batteries have received increasing attention due to their high intrinsic safety, good flexibility, and high theoretical energy density.

[0003] As a key component of polymer-based lithium metal batteries, polymer electrolytes have received extensive attention from academia and the business community. Studies have shown that stably preserving a small amount of electrolyte in a polymer electrolyte matrix to form a quasi-solid polymer electrolyte is an effective strategy to improve the comprehensive performance of electrolytes and batteries. As the core component of this type of electrolyte, the design and preparation of the polymer matrix is ​​crucial. Currently, the materials that are being studied more include polyethylene oxide (PEO), polyvinyl pyrrolidone (PVP), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polyvinylidene fluoride (PVDF) or polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), etc. Among them, PVDF-HFP has the advantages of high dielectric constant, good mechanical properties, and stable electrochemical properties, and has received extensive attention and focused research from researchers.

[0004] In order to solve the shortcomings of this type of polymer in terms of high crystallinity, low electrolyte affinity, and poor stability at the electrode interface, a polyethylene glycol (PEG)-based polymer with complementary properties is often used to form a PVDF-HFP-PEG polymer to improve its overall performance. At present, the main strategies for introducing PEG into PVDF-HFP to form PVDF-HFP-PEG polymers include physical blending, physical crosslinking, and chemical crosslinking. Although these crosslinking strategies can combine the advantages of the two to a certain extent, there are still important challenges. Among them, the simple blending strategy will cause the two phases to be completely miscible, resulting in phase separation problems, while the physical and chemical crosslinking strategy has the problem of poor stability caused by the introduction of impurities and weak bonding. The emergence of these problems will ultimately seriously affect the key performance of the corresponding lithium metal battery, such as power density, cycle life, and safety.

[0005] To address the above challenges, this invention proposes a unique cross-linking strategy - "mild cross-linking method", which can successfully achieve significant improvements in the key performance of the obtained PVDF-HFP-@PEG-based electrolyte in terms of ionic conductivity, mechanical properties, chemical / thermal stability, etc. without introducing any catalysts or cross-linking agents. Summary of the invention

[0006] In response to existing scientific and technological problems, the present invention proposes a "mild cross-linking method" strategy for the first time in the field of lithium metal battery electrolytes, and applies it to the construction of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP)-based slightly cross-linked polymer (PVDF-HFP-@PEG) membranes with specific structures, achieving significant improvements in the mechanical and electrochemical properties of the corresponding electrolytes. The resulting polymer electrolyte can effectively promote the optimization of the key electrochemical properties of the corresponding lithium metal batteries.

[0007] The present invention adopts the following technical solutions:

[0008] A method for preparing a PVDF-HFP-@PEG-based electrolyte, wherein a PVDF-HFP-@PEG polymer membrane is immersed in an electrolyte under an inert atmosphere and dried to obtain a PVDF-HFP-@PEG-based electrolyte, wherein the general structural formula of the PVDF-HFP-@PEG polymer membrane is:

[0009]

[0010] Wherein, x is a positive integer greater than 0 and less than n, y is a positive integer greater than 0 and less than m, at least one of x and y is greater than or equal to 1, and the values ​​of m and n are determined based on the PVDF-HFP used.

[0011] The preparation method of the PVDF-HFP-@PEG polymer membrane is:

[0012]

[0013] The preparation method of the PVDF-HFP-@PEG polymer membrane is specifically as follows: first, PVDF-HFP and NH2-PEG-NH2 are added to a solvent and mixed evenly, then the obtained precursor mixture is spread into a thin liquid layer and vacuum dried at room temperature, and finally, a cross-linking reaction is carried out under vacuum conditions of 130 to 230°C to obtain a PVDF-HFP-@PEG polymer membrane. The mass ratio of PVDF-HFP to NH2-PEG-NH2 is 2 to 6:1. Preferably, the vacuum drying time at room temperature is 12 to 48 hours, and the cross-linking reaction is 0.5 to 5 hours.

[0014] The solvent is one of N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), acetonitrile (CH3CN), N,N-dimethylacetamide (DMAC), dimethyl sulfoxide (DMSO), and hexamethylphosphoric acid triamide (HMPA).

[0015] The electrolyte includes a metal salt and an organic solvent, and the metal salt includes but is not limited to one of a lithium salt, a sodium salt, and a zinc salt. The lithium salt is one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium tetrafluoroborate (LiBF4), lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), and lithium bis(difluorosulfonyl)imide (LiFSI), and the lithium salt concentration in the electrolyte is 0.5 to 3 mol / L; the sodium salt is sodium hexafluorophosphate (NaPF6), sodium trifluoromethanesulfonate (NaOTF), and difluoroborate (LiFSI). Sodium sulfonyl imide (NaFSI), sodium bistrifluoromethylsulfonyl imide (NaTFSI), sodium tetrafluoroborate (NaBF4), sodium bisoxalatoborate (NaBOB), sodium difluorooxalatoborate (NaDFOB), sodium perchlorate (NaClO4), and the concentration of sodium salt in the electrolyte is 0.5-3 mol / L; zinc salt is zinc sulfate (ZnSO4), zinc trifluoromethanesulfonate (ZnOTF), and the concentration of zinc salt in the electrolyte is 0.5-3 mol / L. The organic solvent is one or more of 1,3-dioxolane (DOL), ethylene glycol dimethyl ether (DME), hydrofluoroether (TTE), ethylene carbonate (EC), ethylene carbonate (VC), fluoroethylene carbonate (FEC), dimethyl carbonate (DMC) and diethyl carbonate (DEC).

[0016] The PVDF-HFP-@PEG-based electrolyte prepared by the preparation method thereof is applied to a battery, wherein the polymer electrolyte is placed between a positive electrode and a negative electrode to assemble into a lithium battery.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] (1) The present invention can prepare a PVDF-HFP-@PEG-based polymer electrolyte with elastomeric properties. The polymer electrolyte has strong mechanical properties, can adapt to the volume changes during long-term lithium plating and stripping, and can maintain good interface contact between the electrolyte and the electrode for a long time, thereby reducing the interface impedance and inhibiting the growth of lithium dendrites.

[0019] (2) The present invention can prepare a PVDF-HFP-@PEG-based polymer electrolyte with an ultra-high dielectric constant, which can significantly enhance the dissociation of lithium salts and increase the free Li + The concentration of lithium ions can be increased, the capacity of the corresponding lithium battery can be improved, and the amount of "dead lithium" can be reduced in the long-term charge and discharge cycle of the corresponding lithium battery to ensure the coulomb efficiency, thereby optimizing the long-term stable cycle performance of the battery.

[0020] (2) The present invention can prepare a PVDF-HFP-@PEG-based polymer electrolyte with a special configuration. The PEG "bridge" chain present in the polymer electrolyte expands the chain spacing of the original PVDF-HFP matrix and introduces a large number of oxygen sites on the PEG chain, providing a more abundant, more diverse and more efficient lithium ion migration path.

[0021] (3) The present invention can prepare a PVDF-HFP-@PEG-based polymer electrolyte with a special configuration. The polymer electrolyte has good mechanical properties, thermal stability and the ability to retain electrolyte components. Regardless of whether it is subjected to external force or high temperature environment, it can well maintain the stability of its own structure and shape and effectively retain the electrolyte components, which can significantly improve the safety of the corresponding lithium battery operation.

[0022] (4) The polymer electrolyte prepared by the present invention has uniformly distributed components, a stable internal structure, and excellent lithium ion dissociation and transmission capabilities. The lithium metal battery assembled therefrom exhibits excellent electrochemical performance in high current tolerance and fast charging performance tests.

[0023] (5) The polymer electrolyte raw materials involved in the present invention have good cost competitiveness, and the preparation process is simple and easy to operate, which is conducive to industrial production and expansion. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a high-rate long-cycle performance diagram of a lithium metal battery assembled using the PVDF-HFP-@PEG-based electrolyte prepared in Example 1.

[0025] Figure 2It is a comparison chart of the long cycle performance of lithium metal batteries assembled with the PVDF-HFP-@PEG-based electrolyte prepared in Example 1 and the PVDF-HFP-based electrolyte prepared in Comparative Example 1.

[0026] Figure 3 It is a planar SEM image of the PVDF-HFP-@PEG polymer membrane prepared in Example 1, the PVDF-HFP polymer membrane prepared in Comparative Example 1, and the PVDF-HFP+PEG polymer membrane prepared in Comparative Example 2.

[0027] Figure 4 This is a comparison chart of thermal stability performance tests of the PVDF-HFP-@PEG polymer membrane prepared in Example 1, the PVDF-HFP polymer membrane prepared in Comparative Example 1, and the PVDF-HFP+PEG polymer membrane prepared in Comparative Example 2.

[0028] Figure 5 It is a Fourier transform infrared test (FT-IR) comparison chart of the PVDF-HFP-@PEG polymer membrane prepared in Example 1, the PVDF-HFP polymer membrane prepared in Comparative Example 1, and the PVDF-HFP+PEG polymer membrane prepared in Comparative Example 2.

[0029] Figure 6 It is a stress-strain curve comparison diagram of the PVDF-HFP-@PEG polymer membrane prepared in Example 1, the PVDF-HFP polymer membrane prepared in Comparative Example 1, and the PVDF-HFP+PEG polymer membrane prepared in Comparative Example 2, respectively.

[0030] Figure 7 The thermogravimetric analysis (TGA) test comparison charts of the PVDF-HFP-@PEG-based electrolyte prepared in Example 1, the PVDF-HFP-based electrolyte prepared in Comparative Example 1, and the PVDF-HFP+PEG-based electrolyte prepared in Comparative Example 2 are respectively shown.

[0031] Figure 8 This is a high-rate long-cycle performance diagram of a lithium metal battery assembled using the PVDF-HFP-@PEG-based electrolyte prepared in Example 2.

[0032] Fig. 9 This is a high-load and long-cycle performance diagram of a lithium metal battery assembled using the PVDF-HFP-@PEG-based electrolyte prepared in Example 3. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments.

[0034] Example 1

[0035] (1) Preparation of PVDF-HFP-@PEG polymer membrane: 300 mg and 100 mg of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP, purchased from Aladdin, CAS No.: 9011-17-0) and double-terminated amino polyethylene glycol (NH2-PEG-NH2) were weighed and mixed in a glove box, and then N,N-dimethylformamide solution (DMF) was added for miscibility to obtain a precursor solution. Then, the obtained precursor solution was continuously stirred at room temperature for 12 hours to form a uniform solution. Finally, the uniformly stirred precursor solution was poured into a glass dish with a diameter of 8 cm, dried under vacuum at room temperature for 12 hours, and then further vacuum cross-linked at high temperature of 200°C for 2 hours to obtain a PVDF-HFP-@PEG polymer membrane.

[0036] (2) Preparation of PVDF-HFP-@PEG-based electrolyte: First, prepare an electrolyte solution (2M LiTFSI / DOL+DME, the volume ratio of the solvent is 3:1). Then, soak the prepared PVDF-HFP-@PEG polymer membrane in the electrolyte solution for 48 hours, and then further dry and cut to obtain the target PVDF-HFP-@PEG-based electrolyte.

[0037] (3) Preparation of positive electrode of battery: Grind LiFePO4 (LFP), conductive carbon black and polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, add appropriate amount of DMF and stir to obtain slurry, which is evenly coated on aluminum foil. Then transfer the coated electrode to an oven for vacuum drying for 24 hours, cut into discs with a diameter of 10 mm and store them in a glove box for later use.

[0038] (4) Lithium metal battery assembly: The cut LFP positive electrode sheets and electrolyte are placed in a glove box, and then the CR2032 button battery is assembled in the order of positive electrode shell, positive electrode, electrolyte, negative electrode, gasket, spring and negative electrode shell.

[0039] The LandCT3002A battery testing system was used to test the charge and discharge performance of the button batteries assembled above at room temperature.

[0040] The prepared polymer electrolyte was used to assemble lithium metal batteries and the electrochemical performance was tested. The corresponding high-rate and long-cycle battery performance data are as follows: Figure 1 As shown in the figure, the capacity retention rate of Li|PVDF-HFP-@PEG|LiFePO4 lithium metal battery is 92% and the coulombic efficiency is 99.9% after 12,000 stable cycles under 30C operating conditions, which is an extremely excellent performance.

[0041] Comparative Example 1

[0042] (1) Preparation of PVDF-HFP polymer membrane: 300 mg of PVDF-HFP was weighed in a glove box, and then DMF was added to dissolve it to obtain a precursor solution. Then, the obtained precursor solution was continuously stirred at room temperature for 12 hours to form a uniform solution. Finally, the stirred precursor solution was poured into a glass dish with a diameter of 8 cm, and dried under vacuum at room temperature for 24 hours to obtain a PVDF-HFP membrane.

[0043] (2) Preparation of PVDF-HFP-based electrolyte: First, prepare an electrolyte solution (2M LiTFSI / DOL+DME, the volume ratio of the solvent is 3:1). Then, soak the prepared PVDF-HFP polymer membrane in the electrolyte solution for 48 hours, and then further dry and cut to obtain the target polymer PVDF-HFP-based electrolyte.

[0044] (3) Preparation of positive electrode of battery: grind LFP, conductive carbon black and polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, add appropriate amount of DMF and stir to obtain slurry, which is evenly coated on aluminum foil. Then transfer the coated electrode to an oven for vacuum drying for 24 hours, cut into discs with a diameter of 10 mm and store them in a glove box for later use.

[0045] (4) Lithium metal battery assembly: The cut LFP positive electrode sheets and electrolyte are placed in a glove box, and then the CR2032 button battery is assembled in the order of positive electrode shell, positive electrode, electrolyte, negative electrode, gasket, spring and negative electrode shell.

[0046] The LandCT3002A battery testing system was used to test the charge and discharge performance of the button batteries assembled above at room temperature.

[0047] The prepared polymer electrolyte was used to assemble a lithium metal battery and perform electrochemical performance tests. The long cycle battery performance data corresponding to Example 1 and Comparative Example 1 are shown in FIG. Figure 2 As shown in the figure, the lithium metal battery corresponding to Example 1 has a capacity retention rate of 98% and a coulombic efficiency of 99.9% after 3000 stable cycles under 1C operating conditions. Compared with the short cycle life of 277 cycles of the lithium metal battery in Comparative Example 1, the capacity retention rate is 53.8%, and the battery cycle stability is significantly improved, and the capacity performance is excellent.

[0048] Comparative Example 2

[0049] (1) Preparation of PVDF-HFP+PEG polymer film: 300 mg of PVDF-HFP and 100 mg of NH2-PEG-NH2 were weighed and mixed in a glove box, and then DMF was added for miscibility to obtain a precursor solution. Then, the obtained precursor solution was continuously stirred at room temperature for 12 hours to form a uniform solution. Finally, the uniformly stirred precursor solution was poured into a glass dish with a diameter of 8 cm, and dried under vacuum at room temperature for 24 hours to obtain a PVDF-HFP+PEG polymer film.

[0050] The sample polymer film was photographed by scanning electron microscopy (SEM). Figure 3 It can be seen from the surface SEM image that a uniform, tightly connected porous structure completely different from the PVDF-HFP polymer membrane prepared in Comparative Example 1 and the PVDF-HFP+PEG polymer membrane prepared in Comparative Example 2 is formed in the PVDF-HFP-@PEG polymer membrane prepared in Example 1. Although the porosity of the polymer membrane in Example 2 is increased, an obvious phase separation phenomenon occurs at the same time.

[0051] Depend on Figure 4 From the thermal stability test of the polymer membrane, it can be seen that the PVDF-HFP polymer membrane prepared in Comparative Example 1 begins to curl obviously at 125°C and starts to melt at 175°C, the PVDF-HFP+PEG polymer membrane prepared in Comparative Example 2 curls at 175°C and is partially charred and carbonized at 275°C, while the PVDF-HFP-@PEG polymer membrane prepared in Example 1 begins to melt at a temperature as high as 325°C, and does not melt as a whole until 375°C, and the overall appearance of the membrane does not change from beginning to end, which intuitively illustrates that the thermal stability of the polymer membrane is greatly improved before and after modification.

[0052] Fourier transform infrared test (FT-IR) was performed, and the results were as follows Figure 5 By comparing the FT-IR results of Example 1 with those of Comparative Example 2, the weakening of the CF2 symmetric stretching vibration peak (1072 cm -1 、1171cm -1 ) and 1670cm -1 The appearance of the peak (imine bond C=N characteristic peak) confirmed the formation of the cross-linked structure of the PVDF-HFP-@PEG polymer membrane prepared in Example 1, and proved the feasibility of the practice of the "mild cross-linking method".

[0053] The polymer film was subjected to mechanical tensile testing using an INSTRON 5967 universal material testing machine. Figure 6It can be seen that the stress-strain curves of the PVDF-HFP polymer film prepared in Comparative Example 1 and the PVDF-HFP+PEG polymer film prepared in Comparative Example 2 show obvious "Lüders bands", indicating that they have strong plasticity, and at the same time, the contribution of plastic strain to the overall strain in the whole stretching process is large. However, the "Lüders band" disappears in the stress-strain curve of the PVDF-HFP-@PEG polymer film prepared in Example 1, and the main strain form is also converted into elastic deformation, indicating that the plasticity of the material is greatly reduced, achieving the purpose of reducing crystallinity. Although adding NH2-PEG-NH2 plasticizer to the PVDF-HFP matrix will reduce the mechanical properties of the polymer film, Example 1 still maintains an excellent polymer film tensile modulus of 14.2MPa, which shows excellent durability during the operation of the lithium battery, and achieves a synergistic improvement in physical and electrochemical properties.

[0054] (2) Preparation of PVDF-HFP+PEG-based electrolyte: First, an electrolyte solution (2M LiTFSI / DOL+DME, solvent volume ratio of 3:1) was prepared. Then, the prepared PVDF-HFP+PEG polymer membrane was immersed in the electrolyte solution for 48 hours, and then further dried and cut to obtain the target PVDF-HFP+PEG-based electrolyte.

[0055] Thermogravimetric analysis (TGA) test: Below 300°C, the decomposition of lithium salt and electrolyte solvent is mainly caused by Figure 7 As shown, when the high temperature reaches 300°C, the PVDF-HFP-@PEG-based electrolyte prepared in Example 1 can still maintain an ultra-high mass retention rate of 94.3%, and has excellent liquid retention ability.

[0056] Example 2

[0057] (1) Preparation of PVDF-HFP-@PEG polymer membrane: 500 mg and 100 mg of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) and double-terminated amino polyethylene glycol (NH2-PEG-NH2) were weighed and mixed in a glove box, and then N,N-dimethylformamide solution (DMF) was added for miscibility to obtain a precursor solution. Then, the obtained precursor solution was continuously stirred at room temperature for 12 hours to form a uniform solution. Finally, the uniformly stirred precursor solution was poured into a glass dish with a diameter of 8 cm, dried under vacuum at room temperature for 12 hours, and then further vacuum cross-linked at high temperature of 200°C for 2 hours to obtain a PVDF-HFP-@PEG polymer membrane.

[0058] (2) Preparation of PVDF-HFP-@PEG-based electrolyte: First, prepare an electrolyte solution (1M LiPF6 / EC+FEC, the volume ratio of the solvent is 3:1). Then, soak the prepared PVDF-HFP-@PEG polymer membrane in the electrolyte solution for 48 hours, and then further dry and cut to obtain the target PVDF-HFP-@PEG-based electrolyte.

[0059] (3) Preparation of battery positive electrode: same as in Example 1.

[0060] (4) Lithium metal battery assembly: same as in Example 1.

[0061] The LandCT3002A battery testing system was used to test the charge and discharge performance of the button batteries assembled above at room temperature.

[0062] The prepared electrolyte was used to assemble lithium metal batteries and perform electrochemical performance tests. The corresponding high-rate and long-cycle battery performance data are as follows: Figure 8 As shown in the figure, the lithium metal battery assembled with the electrolyte prepared in Example 2 has a capacity retention rate of 74% and a coulombic efficiency of 99.9% after 9000 stable cycles at 20C, and the performance is extremely excellent.

[0063] Example 3

[0064] (1) Preparation of PVDF-HFP-@PEG polymer membrane: 200 mg and 100 mg of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) and double-terminated amino polyethylene glycol (NH2-PEG-NH2) were weighed and mixed in a glove box, and then N,N-dimethylformamide solution (DMF) was added for miscibility to obtain a precursor solution. Then, the obtained precursor solution was continuously stirred at room temperature for 12 hours to form a uniform solution. Finally, the uniformly stirred precursor solution was poured into a glass dish with a diameter of 8 cm, dried under vacuum at room temperature for 12 hours, and then further vacuum cross-linked at high temperature of 180°C for 1 hour to obtain a PVDF-HFP-@PEG polymer membrane.

[0065] (2) Preparation of PVDF-HFP-@PEG-based electrolyte: First, prepare an electrolyte solution (1M LiFSI / DME+TTE, the volume ratio of the solvent is 5:1). Then, soak the prepared PVDF-HFP-@PEG polymer membrane in the electrolyte solution for 48 hours, and then further dry and cut to obtain the target PVDF-HFP-@PEG-based electrolyte.

[0066] (3) Preparation of battery positive electrode: same as in Example 1.

[0067] (4) Lithium metal battery assembly: same as in Example 1.

[0068] The LandCT3002A battery testing system was used to test the charge and discharge performance of the button batteries assembled above at room temperature.

[0069] The prepared electrolyte was used to assemble lithium metal batteries and perform electrochemical performance tests. The corresponding high-load and long-cycle battery performance data are as follows: Fig. 9 As shown in the figure, the lithium metal battery assembled with the electrolyte prepared in Example 3 has a -1 Under the operating conditions of higher positive electrode loading, the capacity retention rate after 130 stable cycles was 93.2%, and the Coulombic efficiency was 99.9%, with excellent performance.

Claims

1. A method for preparing a PVDF-HFP-@PEG-based electrolyte, characterized in that: The PVDF-HFP-@PEG polymer membrane is immersed in an electrolyte under an inert atmosphere and dried to obtain a PVDF-HFP-@PEG-based electrolyte. The general structural formula of the PVDF-HFP-@PEG polymer membrane is: Wherein, x is a positive integer greater than 0 and less than n, y is a positive integer greater than 0 and less than m, at least one of x and y is greater than or equal to 1, and the values ​​of m and n are determined based on the PVDF-HFP used.

2. The method for preparing the PVDF-HFP-@PEG-based electrolyte according to claim 1, characterized in that: The preparation method of the PVDF-HFP-@PEG polymer membrane is:

3. The method for preparing the PVDF-HFP-@PEG-based electrolyte according to claim 1, characterized in that: First, PVDF-HFP and NH2-PEG-NH2 are added to a solvent and mixed evenly. Then, the obtained precursor mixture is spread into a thin liquid layer and vacuum dried at room temperature. Finally, a cross-linking reaction is carried out under vacuum conditions at 130-230°C to obtain a PVDF-HFP-@PEG polymer membrane. The mass ratio of PVDF-HFP and NH2-PEG-NH2 is 2-6:

1.

4. The method for preparing the PVDF-HFP-@PEG-based electrolyte according to claim 3, characterized in that: The vacuum drying time at room temperature is 12 to 48 hours, and the cross-linking reaction time is 0.5 to 5 hours.

5. The method for preparing the PVDF-HFP-@PEG-based electrolyte according to claim 3, characterized in that: The solvent is one of N,N-dimethylformamide, N-methylpyrrolidone, acetonitrile, N,N-dimethylacetamide, dimethyl sulfoxide and hexamethylphosphoric triamide.

6. The method for preparing the PVDF-HFP-@PEG-based electrolyte according to claim 1, characterized in that: The electrolyte comprises a metal salt and an organic solvent, and the metal salt is one of a lithium salt, a sodium salt and a zinc salt.

7. The method for preparing the PVDF-HFP-@PEG-based electrolyte according to claim 6, characterized in that: The lithium salt is one or more of lithium bis(trifluoromethanesulfonyl imide), lithium tetrafluoroborate, lithium hexafluorophosphate, lithium perchlorate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, and lithium bis(difluorosulfonyl imide), and the concentration of the lithium salt in the electrolyte is 0.5-3 mol / L; the sodium salt is one or more of sodium hexafluorophosphate, sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl imide), sodium bis(trifluoromethanesulfonyl imide), sodium tetrafluoroborate, sodium bis(oxalatoborate), sodium difluorooxalatoborate, and sodium perchlorate, and the concentration of the sodium salt in the electrolyte is 0.5-3 mol / L; the zinc salt is one or more of zinc sulfate and zinc trifluoromethanesulfonate, and the concentration of the zinc salt in the electrolyte is 0.5-3 mol / L, and the organic solvent is one or more of 1,3-dioxolane, ethylene glycol dimethyl ether, hydrofluoroether, ethylene carbonate, ethylene carbonate, fluoroethylene carbonate, dimethyl carbonate, and diethyl carbonate.

8. A PVDF-HFP-@PEG-based electrolyte prepared according to the preparation method according to any one of claims 1 to 6.

9. A lithium battery, comprising a positive electrode, a negative electrode and a PVDF-HFP-@PEG-based electrolyte, wherein the PVDF-HFP-@PEG-based electrolyte is placed between the positive electrode and the negative electrode to form a battery.

Citation Information

Patent Citations

  • Polymer electrolyte film material and preparation method thereof

    CN112397780A

  • Preparation method of solid electrolyte

    CN114479136A

  • Preparation method of doped graphene-polyethylene glycol-based polymer conversion film

    CN114944537A

  • Graft-NH2 solid polymer electrolyte and preparation method thereof

    CN116169371A